The Fever Chart : Three Visions of the Middle East ; With One Short Sleepe. - Wallace, Naomi (Theatre Communications Group, 2009)
Naomi Wallace, the rare writer who combines lyrical theatricality with political ferocity, turns her sight to the Middle East, with a new triptych for the stage. Vision One, A State of Innocence, is set-as the playwright describes, in "something like a small zoo, but more silent, empty, in Rafah, Palestine. Or a space that once dreamed it was a zoo"--And features a Palestinian woman, an Israeli architect, and an Israeli soldier. Vision Two, The Retreating World, is of an Iraqi bird keeper from Baghdad and his address before the International Pigeon Convention. Vision Three, Between th.